Climate change between the mid and late Holocene in northern high latitudes – Part 2: Model-data comparisons - K. Holmgren; J. Nilsson; H. Körnich; A. Moberg; H. S. Sundqvist; Q. Zhang (Climate of the Past, 2010)
The climate response over northern high latitudes to the mid-Holocene orbital forcing has been investigated in three types of PMIP (Paleoclimate Modelling Intercomparison Project) simulations with different complexity of the modelled climate system. By first undertaking model-data comparison, an objective selection method has been applied to evaluate the capability of the climate models to reproduce the spatial response pattern seen in proxy data. The possible feedback mechanisms behind the climate response have been explored based on the selected model simulations. Subsequent model-model comparisons indicate the importance of including the different physical feedbacks in the climate models. The comparisons between the proxy-based reconstructions and the best fit selected simulations show that over the northern high latitudes, summer temperature change follows closely the insolation change and shows a common feature with strong warming over land and relatively weak warming over ocean at 6 ka compared to 0 ka. Furthermore, the sea-ice-albedo positive feedback enhances this response. The reconstructions of temperature show a stronger response to enhanced insolation in the annual mean temperature than winter and summer temperature. This is verified in the model simulations and the behaviour is attributed to the larger contribution from the large response in autumn. Despite a smaller insolation during winter at 6 ka, a pronounced warming centre is found over Barents Sea in winter in the simulations, which is also supported by the nearby northern Eurasian continental and Fennoscandian reconstructions. This indicates that in the Arctic region, the response of the ocean and the sea ice to the enhanced summer insolation is more important for the winter temperature than the synchronous decrease of the insolation.